A solar-blind photodetector with ultrahigh rectification ratio and photoresponsivity based on the MoTe2/Ta:β-Ga2O3 pn junction. (April 2023) - Zeng, Guang; Zhang, Meng-Ru; Chen, Yu-Chang; Li, Xiao-Xi; Chen, Ding-Bo; Shi, Cai-Yu; Zhao, Xue-Feng; Chen, Na; Wang, Ting-Yun; Zhang, David Wei; Lu, Hong-Liang
Abstract: High-performance solar-blind photodetectors have attracted increasing attention due to their important implications in military, medical, and industrial applications. Among a large number of wide-bandgap semiconductors, the quasi-two-dimensional β -Ga2 O3 material is considered as a novel candidate for the solar-blind region (200–280 nm) owing to its suitable bandgap and superior optoelectronic properties. Herein, we report an outstanding solar-blind photodetector based on the MoTe2 /Ta: β -Ga2 O3 pn junction, which exhibits excellent optoelectrical properties with a superhigh rectification ratio ∼1.0 × 10 7, an ultrahigh responsivity ( R ∼358.9 A/W), a large detectivity ( D * ∼3.1 × 10 12 Jones), an excellent external quantum efficiency ( EQE ∼1.76 × 10 5 %), a fast photoresponse (21.1/84.5 ms), and a high rejection ratio (∼1.1 × 10 3 ) under forward bias (1.5 V) and deep-ultraviolet (UV) illumination. These superior photoresponses result from the rapid separation of photoexcited electron-hole pairs driven by the synergistic effect of the forward bias and built-in electric field of the pn junction. Moreover, the MoTe2 /Ta: β -Ga2 O3 pn junction photodetector also demonstrates competitive optoelectronic characteristics in self-powered mode with an ultralow dark current of 8.5 fA and a fairly high R of 9.2 mA/W. As a result, this work provides an alternative solution for designing and fabricating high-performance solar-blind photodetectors with potential applications in UV imaging, environmental monitoring, and insecure communication.